Orthonormalization of a Subset of Bernstein Polynomial Basis Functions - St George, Thomas; Wendland, Alec (The PUMP Journal of Undergraduate Research, 2024)
An explicit formula for an orthornomalized subset Bernstein polynomial basis is derived in order to solve linear boundary value problems with Dirichlet conditions via the Galerkin method.